2013
DOI: 10.1007/s13277-013-0808-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of FOXQ1 is a prognostic marker for patients with gastric cancer

Abstract: Altered expression of forkhead box Q1 (FOXQ1) is observed in various types of human cancers. However, the clinical significance of FOXQ1 expression in gastric cancer (GC) remains largely unknown. The present study aims to explore the clinicopathological significance and prognostic value of FOXQ1 in GC. FOXQ1 messenger RNA (mRNA) and protein expression were determined by quantitative real-time reverse transcriptase-polymerase chain reaction and Western blot in 20 pairs of fresh frozen GC tissues and correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 14 publications
4
30
0
Order By: Relevance
“…A recent study found that FOXQ1 was overexpressed in GC tissues, and this overexpression was closely related to tumor size, histological grade, lymph node involvement, TNM stage, and shorter overall survival of GC patients [14]. However, no further biological function of FOXQ1 in human GC has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that FOXQ1 was overexpressed in GC tissues, and this overexpression was closely related to tumor size, histological grade, lymph node involvement, TNM stage, and shorter overall survival of GC patients [14]. However, no further biological function of FOXQ1 in human GC has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, FOXQ1 is associated with an aggressive cancer phenotype and regulates epithelial-mesenchymal transition (EMT) by suppressing E-cadherin transcription [8,12,13]. In clinical settings, overexpression of FOXQ1 protein has been reported to be strongly linked to poor prognosis in cancers such as non-small cell lung cancer [9], hepatocellular carcinoma [11], and gastric cancer [14]. To date, however, the biological function of FOXQ1 in GC and the mechanism underlying its upregulation have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…High FOXQ1 expression is tightly linked to the aggressive malignant phenotype of hepatocellular carcinoma (30). FOXQ1 expression is significantly upregulated in gastric cancer tissues and is positively related to tumor size, histological grade, lymph node metastasis, and poor prognosis of gastric cancer (15). Furthermore, high expression of FOXQ1 promotes the proliferation and metastasis of glioma (7) and esophageal cancer cells (5).…”
Section: Discussionmentioning
confidence: 99%
“…The increased EMT of cancer cells accounts for cancer metastasis by promoting the migratory and invasive abilities of cancer cells (10,11). FOXQ1 has been suggested as an oncogene in various cancers, including colorectal (12), lung (13,14), gastric (15), ovarian (16) and breast cancers (17). However, whether or not FOXQ1 plays an important role in cervical cancer remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of FOXQ1 was a prognostic factor for overall survival and correlated with tumor size, grade and tumor-node metastasis stage (Liang et al, 2013). …”
Section: Prognosismentioning
confidence: 99%